'Fae nae hair te grey hair they answered the call': International Brigade Volunteers from the West Central Belt of Scotland in the Spanish Civil War, 1936–9. Issue 1 (May 2015) - Raeburn, Fraser
<x xml:space="preserve">Abstract</x> Despite making up over ten per cent of the British volunteers in the International Brigades during the Spanish Civil War (1936-9), Scots from Glasgow and the surrounding districts have been overlooked in many accounts of the British involvement in the conflict. In seeking to explain the disproportionate numbers of volunteers from this region, the influence of factors such as economic conditions, political structures and institutions, ideology and community are examined with reference to individuals' decisions to volunteer in Spain. It is argued that as well as the more severe impact of the inter-war slump in the region, it was Glasgow's distinctive working-class cultures, which placed great importance on grassroots political communities, with an emphasis on social as well as political connections, that led to Communist Party recruitment efforts being especially successful.